Analysis of Physical Education Learning Outcomes Running 40 Meter - Nur Indah Atifah Anwar; Juhanis Juhanis; M.Adam Mappaompo; Iskandar Iskandar; Andi Saparia (Universitas PGRI Palembang, 2022)
Analysis of Physical Education Learning Outcomes 40 M Running Number Students of SDI Minasa Upa Makassar City. This study is a quantitative study aimed at determining the level of Physical Education Learning Outcomes 40 M Students of SDI Minasa Upa Makassar City. The population in this study were all 414 students of SDI Minasa Upa while the research sample consisted of 30 people. Data collection techniques using questionnaires and observation sheets. The data analysis technique used is descriptive statistics using computer facilities through the SPSS version 20.00 program. Based on the results of the data and discussion of this study, it can be concluded that the level of Physical Education Learning Outcomes 40 M Students of SDI Minasa Upa Makassar City is in the very high category.